High temperature treatments of porous activated carbon - García-Mateos, Francisco José; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2018)
The use of biomass waste for the preparation of activated carbon is of great industrial interest for reducing costs and increasing the sustainability, especially in the field of energy storage. A high temperature treatment is required to obtain a more ordered carbon material, thus increasing its conductivity. However, this high temperature treatment entails as a disadvantage a significant reduction in porosity. Therefore, a method to prepare activated carbons with a high porosity development as well as high conductivity could be of great interest for many applications. The aim of this work is to analyze the possible influence of phosphorus compounds on the physical-chemical properties of different carbon materials thermally treated at relatively high temperatures (1600 ºC). With this goal, it has been prepared activated carbons from different precursors (olive stone, lignin and hemp) and different conformations (powder, fibers and monoliths) by physical and chemical activation, with CO2 and H3PO4, respectively. Once the different activated carbon materials were prepared, they were thermally treated at 1600 ºC under inert atmosphere. The different samples were characterized by N2 and CO2 adsorption at 77 and 273 K, respectively, XPS, XRD and Raman techniques. The oxidation resistance was also evaluated in a thermogravimetric balance. High temperature treatments of activated carbon without the presence of P surface groups produced an important contraction of the porosity (from 900 to 150 m2 g-1). However, temperature treatments of phosphorus-activated carbon allowed for preparing carbon materials with a relatively high structural order and a well-developed porosity (c.a. 1100 m2 g-1), with a significant contribution of mesoporosity. These results suggest that these P-surface groups are responsible for the low contraction observed for the porous structure, avoiding, in a large extent, its collapse.
Keywords: Carbón activado; Activated carbon; High temperature; Phosphorus surface groups